An Inclusive Group Guidance Model Based on Social Interaction to Improve the Mental Health of Children with Special Needs in Community Settings - I Made Mahaardhika; I Dewa Ayu Eka Purba Dharma Tari; Chenda Dara (Yayasan Adra Karima Hubbi, 2026)
Background: Children with special needs (CSN) face significant challenges in mental health, particularly related to limited social interaction, low self-confidence, and a high risk of social isolation. Existing guidance and counseling services have not fully integrated social and emotional approaches within inclusive and contextual settings. Purpose: This study aims to develop an inclusive group guidance model based on social interaction to enhance the mental health of children with special needs in a community setting. Method: This study employed a qualitative approach with a case study design combined with model development. Data were collected through participant observation, in-depth interviews, and documentation during group guidance activities involving children with special needs and facilitators in an inclusive community environment. Data analysis was conducted using thematic analysis to identify patterns of social interaction and their impact on participants’ psychological conditions. Results: The findings indicate that structured social interaction within group guidance significantly improves social engagement, emotional regulation, and self-confidence among children with special needs. Social support from facilitators and group members also contributes to the creation of a safe and inclusive psychological environment. Conclusion: The inclusive group guidance model based on social interaction is effective in improving the mental health of children with special needs and can serve as an innovative alternative in community-based counseling services. Novelty: This study proposes an integrative model that combines social psychology, mental health, and group guidance within a community setting as a novel, practical, and contextual approach to inclusive counseling services.